Lithium-like O5+ Emission near 19 Å - Jaan K. Lepson; Gregory V. Brown; Joel H. T. Clementson; Alexander J. Fairchild; Ming Feng Gu; Natalie Hell; Elmar Träbert; Peter Beiersdorfer (Atoms)
Using a high-resolution grating spectrometer on the Livermore EBIT-I electron beam ion trap, we have measured three <semantics>n=3,4→n=1</semantics> K-shell emission lines in lithium-like O<semantics>5+</semantics>, which are situated near the O VIII Lyman-<semantics>α</semantics> lines at 19 Å. Two of the resulting wavelengths agree well with the wavelengths of these lines we reported earlier, but the wavelength of the third line does not. In contrast, our new wavelengths now fully agree with those from resonant photo-absorption experiments on the PETRA III synchrotron facility.